Access to medicines by ambulatory health service users in Mexico: an analysis of the national health surveys 1994 to 2006 Acceso a medicamentos para los usuarios del primer nivel de los servicios de salud: análisis de las encuestas nacionales de salud 1994, 2000 y 2006 - Veronika J Wirtz; Giuliano Russo; Ma de la Luz Kageyama-Escobar (Instituto Nacional de Salud Pública, 2010)
OBJECTIVE: To analyse the medicines prescription, prescription filling, payment expenditure for medicines by ambulatory health service users (HSU) in 2006, and to evaluate its evolution in the last 12 years. MATERIAL AND METHODS: Using data from the National Health Surveys in 2006 three binary logistic regression models were constructed to identify the variables associated with the prescription rate, prescription filling and payment for medicines in 2006. The results of access to medicines were compared to the ones from previous National Health Services from 1994 and 2000. RESULTS: The type of health service provider was found to be the most important predictors of access to medicines. Although the proportion of HSU obtaining a prescription and paying for drugs has broadly stayed the same as in 1994, the percentage of HSU paying for their prescribed medicines decreased from 70% in 1994 to 42% at Ministry of Health institutions in 2006. CONCLUSION: The progress in prescription and population access to medicines has been uneven across health service providers. OBJETIVO: Analizar la prescripción médica, surtimiento de recetas y gasto en medicamentos que tienen los usuarios del primer nivel de los servicios de salud (UPNS) en 2006 y evaluar su evolución en los últimos 12 años. MATERIAL Y MÉTODOS: Utilizando los datos de la Encuesta Nacional de Salud de 2006 se construyeron tres modelos de regresión logística para identificar los factores asociados con la prescripción, el surtimiento de medicamentos y el pago por medicamentos recetados. Se compararon los resultados del acceso a medicamentos con los de encuestas anteriores de 1994 y 2000. RESULTADOS: La variable más relevante para el acceso a medicamentos fue el tipo de institución donde se prestó atención. Aunque al nivel global la proporción de los UPNS que obtuvieron una prescripción y que pagaron por los medicamentos más o menos se mantuvo estable, el porcentaje de los UPNS que pagaron por los medicamentos en las instituciones de la Secretaría de Salud disminuyó de 70 a 42% entre 1994 y 2006. CONCLUSIÓN: El mejoramiento del acceso a medicamentos para usuarios de los servicios de salud ha sido desigual a través de las instituciones.